THE UNDERSTANDING OF ISLAMIC EDUCATION TEACHERS TO THE PRINCIPLES AND FOUNDATIONS OF CURRICULUM DEVELOPMENT AT SMK NEGERI 1 REJANG LEBONG - Putri, Oktia Anisa; Sutarto, Sutarto; Idris, Muhammad (INCARE, International Journal of Educational Resources, 2023)
The purpose of this study was to find out about how Islamic Religious Education teachers' understanding of the principles and foundations of curriculum development at SMK Negeri 1 Rejang Lebong. To find out this, the researcher used a descriptive qualitative research method, namely to clearly describe and describe things that happened in the field. Data collection techniques used include; first, Observation, namely the activities that the author does directly jump into the field and observe the variables to be studied. The data that has been collected is then analyzed using data reduction analysis techniques, data presentation and data verification. The results of the study reveal that an educator's understanding of the principles and foundations in curriculum development must be emphasized, because without a deep understanding it will be very impossible for curriculum development to be carried out and achieve learning objectives. With a broad and deep understanding, if there is something in the curriculum that is not in accordance with the times, it will be very easy for an educator to correct the discrepancy with what is happening in the field.